2021
DOI: 10.1186/s12931-021-01919-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the lung microbiome with PD-L1 expression and immunotherapy response in lung cancer

Abstract: Background Lung cancer is the primary cause of cancer-related deaths worldwide. The human lung serves as a niche to a unique and dynamic bacterial community that is related to the development of multiple diseases. Here, we investigated the differences in the lung microbiomes of patients with lung cancer. Methods 16S rRNA sequencing was performed to evaluate the respiratory tract microbiome present in the bronchoalveolar lavage fluid. Patients were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Previous studies have reported that C. aerofaciens augments the T cell response and improves anti-programmed cell death ligand-1 (PD-L1) therapy efficacy. 46 In addition, V. dispar is dominant in the PD-L1 immunotherapy responder group 47 and is associated with influenza-specific H1 and H3 IgA antibody responses. 48 Although we used machine learning classifiers to investigate the potential utility of gut microbial in predicting the ACE2-RBD inhibiting antibody response, a lack of an independent test cohort is a limitation, further cause-and-effect study is still needed to investigate the mechanism of how the microbiota modulates the BBIBP-CorV vaccine response.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that C. aerofaciens augments the T cell response and improves anti-programmed cell death ligand-1 (PD-L1) therapy efficacy. 46 In addition, V. dispar is dominant in the PD-L1 immunotherapy responder group 47 and is associated with influenza-specific H1 and H3 IgA antibody responses. 48 Although we used machine learning classifiers to investigate the potential utility of gut microbial in predicting the ACE2-RBD inhibiting antibody response, a lack of an independent test cohort is a limitation, further cause-and-effect study is still needed to investigate the mechanism of how the microbiota modulates the BBIBP-CorV vaccine response.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the microbiome plays a crucial role in cancer cells’ response to immunotherapy. For example, Jang et al analyzed the microbiome’s relationship with programmed death-ligand-1 (PD-L1) expression [ 81 ]. PD-L1 protein is typically involved in protecting non-cancerous/non-harmful cells from immune cells.…”
Section: Balf Biomarkers For the Diagnosis And Prognosis Of Lung Cancermentioning
confidence: 99%
“…Notably, Akkermansia was more enriched in squamous cell carcinoma in comparison to adenocarcinoma [56]. A recent study attempted to assess the microbiome profile using Bronchoalveolar lavage fluid samples in relation to PD-L1 expression in NSCLC patients (n = 84) [57]. While alpha and beta diversities did not differ significantly between high and low PD-L1 expression patients, the population of Neissseria was significantly higher in low PD-L1 expression patients [57].…”
Section: Lung Cancermentioning
confidence: 99%
“…A recent study attempted to assess the microbiome profile using Bronchoalveolar lavage fluid samples in relation to PD-L1 expression in NSCLC patients (n = 84) [57]. While alpha and beta diversities did not differ significantly between high and low PD-L1 expression patients, the population of Neissseria was significantly higher in low PD-L1 expression patients [57]. Chau et al reported on NSCLC patients responding to chemoimmunotherapy, in which Finegoldia was enriched in the nasal microbiome, yet buccal samples showed increased Megasphaera but reduced Actinobacillus in responders [58].…”
Section: Lung Cancermentioning
confidence: 99%